Amazon deforestation enriches antibiotic resistance genes. (February 2021) - Lemos, Leandro Nascimento; Pedrinho, Alexandre; Vasconcelos, Ana Tereza Ribeiro de; Tsai, Siu Mui; Mendes, Lucas William
Abstract: The expansion of livestock production and agriculture is responsible for the increase of deforestation rates in the Amazon rainforest, with consequences to climate and micro and macro biodiversity. Although many studies have evaluated the effects of deforestation on the microbiome, its effect on the soil resistome remains unknown. Considering that antibiotic resistance genes (ARGs) are a threat to global health and food security, here we evaluated how land-use change in the Amazon region impacts the soil resistome. Our analysis revealed that several antibiotic resistance mechanisms and genes are common to both the native forest and the altered areas; however, deforestation and subsequent conversion to other land-use systems increased the diversity and abundance of these genes. The enrichment of ARGs is correlated to increased microbial diversity in response to deforestation, along with changes in soil chemical properties, such as pH and aluminum. Our findings demonstrated that Amazon deforestation enriched ARGs in soil and how anthropogenic disturbances may exert selective pressure on the microbial communities expanding the soil resistome. Further investigation is still needed to understand if the ARGs can be transferred via the food chains ( e.g. agricultural soils) to humans, jeopardizing antibiotic treatment effectiveness and compromising public health. Highlights: Amazon soils are repository of a high diversity of antibiotic resistance genes. Amazon deforestation alters the structure of the resistome. Deforestation increases the diversity and abundance of antibiotic resistance genes. Enrichment of ARGs correlates with microbial community structure and soil properties.